2005
DOI: 10.1111/j.1467-9310.2005.00406.x
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring and organisational learning in research and development

Abstract: This paper presents and discusses the contribution of ‘mentoring’ relationships to organisational learning and knowledge creation in the early stages of research and development (R&D) projects. Our study considers the characteristics of a scientific leader, the nature of the context he creates, and how dialogue contributes to scientific breakthrough. Our study is unusual in as much as research on knowledge creation has developed separately, yet in parallel, with that of mentoring. It is rare to combine these d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…O'Connor and McDermott focus on what we refer to as technical value, i.e., generally related to product characteristics and performance. The same goes for Borredon and Ingham (2005) in their discussion on mentoring in an R&D context. They advocate the central role of dialogue between senior and junior inventors, which in their terms is something ‘far beyond the classical exchange of ideas and information’ (p. 499), implying that there is more to the generative dialogue than technical matters.…”
Section: The Need To Populate the Npd Worldmentioning
confidence: 74%
“…O'Connor and McDermott focus on what we refer to as technical value, i.e., generally related to product characteristics and performance. The same goes for Borredon and Ingham (2005) in their discussion on mentoring in an R&D context. They advocate the central role of dialogue between senior and junior inventors, which in their terms is something ‘far beyond the classical exchange of ideas and information’ (p. 499), implying that there is more to the generative dialogue than technical matters.…”
Section: The Need To Populate the Npd Worldmentioning
confidence: 74%
“…It is suggested that it is desirable to support the creation of innovation through effective communication within and outside the organization. Borredon and Ingham(2005) emphasized the importance of interactions and communication within the leader's team to promote mentoring and learning in research and development. This interaction emphasizes the diffusion of learning within the organization.…”
Section: Internal Technology Cooperation (Internal Relation)mentioning
confidence: 99%
“…A few studies have examined mentoring as a process for personal learning (Lankau & Scandura, ), described the narrative aspects of mentoring (Swap, Leonard, Shields, & Abrams, ), and evaluated how mentoring influences organizational learning and preserves intellectual capital for an organization (Borredon & Ingham, ). In these studies there is some indirect consideration of the information transfer that takes place in mentoring, but no analysis of actual information practices in the mentoring relationship.…”
Section: Literature Reviewmentioning
confidence: 99%